1994
DOI: 10.1093/ajcn/60.6.837
|View full text |Cite
|
Sign up to set email alerts
|

Uncritical use of bone mineral density in absorptiometry may lead to size-related artifacts in the identification of bone mineral determinants

Abstract: Epidemiological studies of bone mineral determinants rely heavily on measurements made with absorptiometric techniques such as single-photon absorptiometry and dual-energy x-ray absorptiometry. In general, absorptiometric data are expressed as areal densities (bone mineral density, BMD), obtained by dividing bone mineral content (BMC) by bone area or width (BA, BW). This size correction assumes that BMC and BA (BW) are directly proportional to one another, such that a 1% change in BA (BW) is matched by a 1% ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
379
1
7

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 542 publications
(398 citation statements)
references
References 5 publications
11
379
1
7
Order By: Relevance
“…A coefficient of 1 for the postmenopausal Chinese women confirmed a linear relationship between tOC and ucOC, but this was not evident in either the British and Gambian postmenopausal data. Coefficient values close to 2 demonstrated that ucOC and tOC were related in an approximately squared manner, which means that 2% increase in ucOC was matched by 1% increase in tOC (Prentice et al, 1994).…”
Section: Relative Concentrations Of Undercarboxylated Osteocalcinmentioning
confidence: 85%
See 1 more Smart Citation
“…A coefficient of 1 for the postmenopausal Chinese women confirmed a linear relationship between tOC and ucOC, but this was not evident in either the British and Gambian postmenopausal data. Coefficient values close to 2 demonstrated that ucOC and tOC were related in an approximately squared manner, which means that 2% increase in ucOC was matched by 1% increase in tOC (Prentice et al, 1994).…”
Section: Relative Concentrations Of Undercarboxylated Osteocalcinmentioning
confidence: 85%
“…The 95% level of significance (Po0.05) was taken as evidence against the null hypothesis. Continuous variables were transformed to a natural logarithm scale to allow expression of proportional differences between groups (Prentice et al, 1994). In all cases, the distributions of the logged variables approximated normality.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Highly intercorrelated independent variables (r Ͼ 0.7) in the multiple model were avoided. To reduce the possibility of body size-related artifacts, the bone area, weight, and height were included in the multiple regression models (24). We also used a variance component model to compare controls and patients while controlling for potential confounders.…”
Section: Methodsmentioning
confidence: 99%
“…Univariate and multiple linear regression analyses were used to investigate the impact of disease variables on bone mass measurements. To avoid the possibility of size-related artifacts, bone area, weight, and height were included in the multiple regression models, as proposed by Prenctice et al (37). Additional variables that are considered to be possible predictors of BMC are listed in Table 4.…”
Section: Methodsmentioning
confidence: 99%